2021
DOI: 10.1155/2021/3798033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped Classroom on Iranian Adolescents: Elementary EFL Learners’ Vocabulary Recall and Retention

Abstract: Vocabulary as an inseparable part of language learning has a vital role in communication, which requires to be taught in new approaches. A quasi-experimental method was used to achieve the aims of the current study. In doing this, 48 Iranian female adolescent elementary learners (13–17) were assigned based on the Oxford Quick Placement Test from 70 female students to take part in 4 sessions of treatment. The participants were randomly divided into two groups: an experimental group (n = 24) and a control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Before answering our research questions, we list the titles and authors of the selected articles (Table 4). The distribution of the number of publications on FC and language teaching shows that in the years analysed the most is in 2021 with 42.3% [23][24][25][26][27][28][29][30][31][32][33], followed by 2022 [34][35][36][37][38] and 2020 [39][40][41][42][43] (19.2%), 11.5% in 2018 [44][45][46] and, finally, 7.7% in 2019 [47,48] Figure 2:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Before answering our research questions, we list the titles and authors of the selected articles (Table 4). The distribution of the number of publications on FC and language teaching shows that in the years analysed the most is in 2021 with 42.3% [23][24][25][26][27][28][29][30][31][32][33], followed by 2022 [34][35][36][37][38] and 2020 [39][40][41][42][43] (19.2%), 11.5% in 2018 [44][45][46] and, finally, 7.7% in 2019 [47,48] Figure 2:…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of the number of publications on FC and language teaching shows that in the years analysed the most is in 2021 with 42.3% [23][24][25][26][27][28][29][30][31][32][33], followed by 2022 [34][35][36][37][38] and 2020 [39][40][41][42][43] (19.2%), 11.5% in 2018 [44][45][46] and, finally, 7.7% in 2019 [47,48] Regarding the countries (Figure 3) in which this research has been carried out, the highest concentration is in Spain [28,35,47], Indonesia [27,33,44], and Iran [23,31,46]; followed by Jordan [24,34], Taiwan [25,36], Turkey [30,48], and Ukraine [26,39]. Moreover, to a lesser extent in Bangladesh [37], Bhutan [41], Cambodia [29], China…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings revealed that students exhibited positive attitudes toward both in-class and out-of-class writing models in the flipped classroom, with a preference for the outof-class model. Soltanabadi et al (2021) conducted a study involving 48 female learners aged 13 to 17 to investigate the impact of the flipped classroom approach on Iranian adolescent elementary students' vocabulary recall and retention. The participants were divided into an experimental group (n=24) and a control group (n=24).…”
Section: Flipped Learningmentioning
confidence: 99%